A Review of SEAAIR Annual Conferences 2007 2021 - Koh Y.Y.; Chua Y.L. (Southeast Asian Association for Institutional Research, 2024)
Since its establishment in 2000, the South East Asia Association for Institution Research (SEAAIR) has organized the SEAAIR Annual Conference in different countries in South East Asia (SEA), including the extension of SEA, which was China (2002), Taiwan (2019) and Korea (2022). Each year, the Conference focuses on different themes based on the country's institutional research and current educational and socio-economic development. The paper reviews the development of SEAAIR conference themes and subthemes to reveal the relatedness of the theme based on the country's contemporary educational or socio-economic development. The analysis of the paper submission based on the country for 2001 2021 is presented to provide an analysis of the trend and active participation level of the countries at the SEAAIR Annual Conference. 2023, Southeast Asian Association for Institutional Research. All rights reserved.